Detectability of the first cosmic explosions - Souza, Rafael S. de; Ishida, E. E. O.; Johnson, J. L.; Whalen, Daniel J.; Mesinger, A. (Monthly notices of the Royal Astronomical Society, 2013)
We present a fully self-consistent simulation of a synthetic survey of the furthermost cosmic explosions. The appearance of the first generation of stars (Population III) in the Universe represents a critical point during cosmic evolution, signalling the end of the dark ages, a period of absence of light sources. Despite their importance, there is no confirmed detection of Population III stars so far. A fraction of these primordial stars are expected to die as pair-instability supernovae (PISNe), and should be bright enough to be observed up to a few hundred million years after the big bang. While the quest for Population III stars continues, detailed theoretical models and computer simulations serve as a testbed for their observability. With the upcoming near-infrared missions, estimates of the feasibility of detecting PISNe are not only timely but imperative. To address this problem, we combine state-of-the-art cosmological and radiative simulations into a complete and self-consistent framework, which includes detailed features of the observational process. We show that a dedicated observational strategy using ≲ 8 per cent of the total allocation time of the James Webb Space Telescope mission can provide us with up to ∼9-15 detectable PISNe per year.
Gesehen am 10.12.2020